(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
In soil, polyacrylamide is a key source of acrylamide because it slowly decomposes into acrylamide. There has been a modest but steady rise in worldwide interest in microbe-mediated acrylamide decomposition as a bioremediation method. A bacterial consortium isolated from the volcanic soil of Mount Marapi, West Sumatra, Indonesia, was able to thrive on acrylamide in this study. Acrylamide-degrading bacteria grew best in the presence of 1 %(w/v) glucose with acrylamide as the sole nitrogen source. Optimum growth occurs in between 300 and 500 mg/L of acrylamide, pH between 6.5 and 8.0, and temperatures between 30 and 35 Â°C. The consortium can also grow on acetamide as the sole nitrogen source. Toxic heavy metals, such as mercury, silver and copper slowed down the growth of this consortium on acrylamide. This is the first report of an acrylamide-degrading consortium isolated from volcanic soils.